ANALISIS DAYASAING KOMODITI TEMBAKAU RAKYAT DI KLATEN JAWA TENGAH - -, SAPTANA; FRIYATNO, SUPENA; BASTUTI P., TRI (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 4, No. 2 Juli 2004, 2012)
Historically tobacco commodities had been interesting as high value commodity since Hindia Belanda Colonialist. Indonesian government to be continued tobacco development implemented by government estate enterprise (Perusahaan Negara Perkebunan). Tobacco farm by smallholder estate in Klaten objective to export commodities. Based on the problem in the tobacco commodities system, this paper have objective to : (1) Performance of tobacco economics; (2) Private and social analysis profitability; (3) Comparative and competitive analysis; (4) Incentives policy analysis in the tobacco commodities system; (5) To formulate development perspective on tobacco commodities. Methodological on this paper use Policy Analysis Matrix (PAM), especially to analysis competitiveness and impact of divergences. The result to describe that tobacco small holder farming in Klaten have comparative and competitive advantage, each to indicate coefficient value of DRC : 0.42-0.65 and PCR : 0.55- 0.67. Even though tobacco market especially for export very high distorted, i.e. cukai cost have achieve 30-40 %. So that rural area in Klaten, Central Java more profitable to increasing for tobacco domestic production compared with import. Policy implication, tobacco production in Klaten can to be continued improvement by specific location of technology development. The several argument are efficiency of domestic resource use, extensive of labor absorption, and so to gate some foreign exchange that is scarcity.
Keywords: Tobacco Cmmodities, Private and Social Analysis, Profitability, Comparative and Competitive Analysis, Policy Analysis Matrix (PAM),